Witchweed [Striga hermonthica (Del.) Benth] control using imazapyr seed coating in maize hybrids in the Nigerian savannah - Chikoye, David; Lum, A.F.; Menkir, A. (Canadian Science Publishing, 2020)
Witchweed [Striga hermonthica (Del.) Benth] is a major parasitic weed of most cereal crops in Africa, including maize. Seed treatment with low doses of acetolactate synthase–inhibiting herbicides, such as imazapyr, was introduced in the 1990s to control witchweed. Field trials were conducted in four locations in Nigeria in 2007 and 2008, to assess the effect of coating seeds of several maize hybrids with imazapyr on witchweed control. The hybrids had genes for imidazolinone herbicide resistance (IR), as well as genetic tolerance to witchweed (ST). Treatments were 12 IR maize hybrids with ST and three checks without the IR gene (commercial, witchweed tolerant, and witchweed susceptible hybrids). Averaged across all locations, the coated IR hybrids with ST yielded more and supported fewer witchweed plants than the uncoated IR hybrids with ST. The IR hybrids with ST yielded 57%–60% more than the commercial and witchweed tolerant hybrid checks that were not coated. The witchweed susceptible hybrid check suffered a yield loss of 88% under infestation without seed coating. The IR hybrids with ST yielded 3564 kg ha−1 of grain when coated with imazapyr and 3266 kg ha−1 otherwise. The findings indicate that coating of IR/ST maize seeds with imazapyr improved tolerance to witchweed.